Validation of UV-Vis Spectrophotometric Method of Quercetin in Ethanol Extract of Tamarind Leaf - Erma Yunita; Deni Yulianto; Siti Fatimah; Tirsa Firanita (Journal of Fundamental and Applied Pharmaceutical Science, 2020)
Tamarindus indica L is a medicinal plant that has many benefits. One of the chemical compounds contained therein is the flavonoid quercetin type. The number of herbal products on the market makes the quality assurance of herbal products need to be done by performing the assay of the active compounds using validated methods. This study aims to validate the assay method quercetin in the extract of tamarind leaves. Tamarind leaf extract was macerated with hexane; then, it was re-macerated with 70% ethanol. The extract was concentrated using a rotary evaporator. The assay was performed using the UV-Vis Spectrophotometry method, and parameter validation specified in this study, including linearity, LOD, LOQ, precision, and accuracy. Quercetin level obtained in extracts of tamarind leaves was at 21.52 mg/g. Based on the test method validation, the correlation coefficient (r) was 0.9999, the regression function coefficients (Vx0) was 0.59545%, LOD 0.1515 ppm, LOQ 0.4592 ppm, coefficient of variation precision was less than 2%, and recoveries range was in 97-103%.Tamarindus indica L is a medicinal plant that has many benefits. One of the chemical compounds contained therein is the flavonoid quercetin type. The number of herbal products on the market makes the quality assurance of herbal products need to be done by performing the assay of the active compounds using validated methods. This study aims to validate the assay method quercetin in the extract of tamarind leaves. Tamarind leaf extract was macerated with hexane; then, it was re-macerated with 70% ethanol. The extract was concentrated using a rotary evaporator. The assay was performed using the UV-Vis Spectrophotometry method, and parameter validation specified in this study, including linearity, LOD, LOQ, precision, and accuracy. Quercetin level obtained in extracts of tamarind leaves was at 21.52 mg/g. Based on the test method validation, the correlation coefficient (r) was 0.9999, the regression function coefficients (Vx0) was 0.59545%, LOD 0.1515 ppm, LOQ 0.4592 ppm, coefficient of variation precision was less than 2%, and recoveries range was in 97-103%.